Android game about HPV for adolescent university health education: experience report (Research, Society and Development, 2022)
Objective: the main objective of the study is to describe the creation experiences and impressions about the use of an application on the prevention of human papillomavirus (HPV). The resource was applied during the theoretical-practical teaching of the discipline of collective health II, exploring the contributions of health education activities developed in the university environment, of the undergraduate nursing course. Methodology: a descriptive study that took place through an experience report. Results and Discussion: The target audience were university students from federal college, and the activities took place in the first half of 2022, in three stages. The first focused on creating the app, the second related to testing the resource and identifying possible errors by employees of the teaching project linked to the discipline, and the third application of the instrument, during the graduation class, via Google Meet®. Conclusion: it is noted that the final product “HPV-Quiz” worked helping in the learning process. There is a need for pedagogical practices in line with the current situation, including the changes experienced with technological and scientific advances.